2021
DOI: 10.1016/j.jbc.2021.100959
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal domain of the Schaaf–Yang syndrome protein MAGEL2 likely has a role in RNA metabolism

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 135 publications
1
26
1
Order By: Relevance
“…Despite being its most deeply studied function, dysregulation of protein trafficking and recycling is not the only consequence of MAGEL2 malfunction. The subcellular localisation of the full MAGEL2 protein [41, 42] and its C-terminal part alone, [39] have been previously studied in heterologous systems, both presenting a mainly cytoplasmic localisation. Our immunocytochemistry assays in different transfected cell lines showed that, in contrast, the heterologously expressed MAGEL2-Gln638* (N-terminal part of the protein) was predominantly located inside the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite being its most deeply studied function, dysregulation of protein trafficking and recycling is not the only consequence of MAGEL2 malfunction. The subcellular localisation of the full MAGEL2 protein [41, 42] and its C-terminal part alone, [39] have been previously studied in heterologous systems, both presenting a mainly cytoplasmic localisation. Our immunocytochemistry assays in different transfected cell lines showed that, in contrast, the heterologously expressed MAGEL2-Gln638* (N-terminal part of the protein) was predominantly located inside the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Our immunocytochemistry assays in different transfected cell lines showed that, in contrast, the heterologously expressed MAGEL2-Gln638* (N-terminal part of the protein) was predominantly located inside the nucleus. The new localisation of the protein suggests that, in addition to the loss of the MAGEL2 normal functions, including the translocation of YTHDF2 to the nucleus, [39] SYS-associated mutations could involve new functions of unknown consequences.…”
Section: ]mentioning
confidence: 99%
See 1 more Smart Citation
“…iPSC-derived neurons from SYS patients displayed fewer and shorter dendrites, which could have a detrimental effect on cognition, information processing, and wiring of the brain, depending on what types of cells in what brain regions are affected. It is important to note that a recent study indicated a novel role of the N terminal domain of the SYS protein MAGEL2 in RNA metabolism [ 131 ], which stands in contrast to the involvement of the C terminal domain that interacts with the WASH complex [ 130 ]. In addition, a recent study reports decreased secretory granule and neuropeptide production in cellular and murine models of PWS, which may, in part, underlie the reported dysfunction of the OT system in models of PWS [ 20 , 21 , 59 ].…”
Section: Dysregulation Of Intracellular Pathways In Murine and Ipsc M...mentioning
confidence: 99%
“…It is a single-exon gene that encodes one of the largest proteins of the type II MAGE protein family consisting of 1249 amino acids. At a structural level, the N-terminal region of MAGEL2 contains a proline-rich domain, whose function remains unclear 39. At the C-terminus, from amino acids 1027 to 1195, there is the MHD, a highly conserved 170-amino acid sequence present in both type I and type II MAGEs, crucial for protein–protein interaction 40.…”
Section: Introductionmentioning
confidence: 99%